2012
DOI: 10.1002/ibd.21847
|View full text |Cite
|
Sign up to set email alerts
|

Toxic megacolon

Abstract: Toxic megacolon represents a dreaded complication of mainly inflammatory or infectious conditions of the colon. It is most commonly associated with inflammatory bowel disease (IBD), i.e., ulcerative colitis or ileocolonic Crohn's disease. Lately, the epidemiology has shifted toward infectious causes, specifically due to an increase of Clostridium difficile-associated colitis possibly due to the extensive (ab)use of broad-spectrum antibiotics. Other important infectious etiologies include Salmonella, Shigella, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(77 citation statements)
references
References 82 publications
0
67
0
8
Order By: Relevance
“…It is therefore difficult to extrapolate the epidemiology of this complication in the elderly population. According to Autenrieth et al [46], the epidemiology of toxic megacolon has shifted towards infection causes, particularly due to an increase of Clostridium difficile-associated colitis and possible use/abuse of antibiotics. A recent survey conducted in the United States concluded that elderly patients with UC are at increased risk for infectious complications and postoperative venous thromboembolism, and that the length of hospital stay was longer in elderly than in subjects aged < 65 years [47].…”
Section: Surgerymentioning
confidence: 99%
“…It is therefore difficult to extrapolate the epidemiology of this complication in the elderly population. According to Autenrieth et al [46], the epidemiology of toxic megacolon has shifted towards infection causes, particularly due to an increase of Clostridium difficile-associated colitis and possible use/abuse of antibiotics. A recent survey conducted in the United States concluded that elderly patients with UC are at increased risk for infectious complications and postoperative venous thromboembolism, and that the length of hospital stay was longer in elderly than in subjects aged < 65 years [47].…”
Section: Surgerymentioning
confidence: 99%
“…26 Fulminant colitis occurs in 2% to 5% of patients with CDI but is associated with a mortality rate of 35% to 80%. 27 A lack of diarrhea in a patient with worsening abdominal distention and systemic illness is an ominous finding and is indicative of ileus and intestinal failure. Patients may be hypotensive and require support with vasopressors and may have other signs and symptoms of end organ failure, including respiratory failure and acute kidney failure.…”
Section: Clinical Manifestations and Spectrum Of Diseasementioning
confidence: 99%
“…We think that colonic necrosis or perforation is not primarily associated with the disease process and occurs only as a result of the development of abdominal compartment syndrome or nonocclusive mesenteric ischemia in patients with complicated disease. 27 The aforementioned criteria for classifying patients as having "complicated" disease are defined in the recent guidelines of the American College of Gastroenterology. 26 The guidelines are based on a combination of multivariate analyses, findings of multiple case series, and the recommendations of the European Society of Clinical Microbiology and Infectious Diseases.…”
Section: Clinical Manifestations and Spectrum Of Diseasementioning
confidence: 99%
“…Toxic megacolon associated with ICD has an incidence of 0.4-3% [11,12] and a mortality rate of 38-80% [12,13].…”
Section: Introductionmentioning
confidence: 99%